Penerapan Booklet Edukasi Kesehatan pada Orang Tua tentang Penanganan Anak Demam dengan Water Tepid Sponge (WTS) - Devania, Angel; Ekawaty, Fadliyana; Sri Mulyani (Program Studi Keperawatan Universitas Jambi, 2023)
Pre-school to school-age children are very susceptible to viruses, such as the dengue virus. Fever is a symptom that may appear in this case. One way to overcome this is with Water Tepid Sponge (WTS). This technique is a compressing action that is done using a towel or washcloth dampened with warm water. This study aims to determine health education about handling children with fever with Water Tepid Sponge. This research uses a case study method directly to patients by means of observation and interviews. Based on the implementation carried out, health education about treating children with fever with Water Edged Sponge (WTS) can be understood by the client's parents well. The results obtained are that all the interventions that have been given are effective in overcoming nursing problems in client. Keywords: Water Tepid Sponge,, Children, Booklet, Health Education